Pengaruh Implementasi SIPSUPER Terhadap Pengelolaan Prasarana, Sarana, dan Utilitas Umum Perumahan - Ade Satriya, Muhammad Andi; Panjaitan, Maraden; Tukimun, Tukimun (METIK JURNAL (AKREDITASI SINTA 3), 2025)
This study aims to examine the implementation of the SIPSUPER (Information System for the Handover of Housing Infrastructure, Facilities, and Public Utilities) application and its impact on the management of PSU in housing areas in Samarinda City. The research is motivated by the low level of developer compliance in handing over PSU to the government, combined with weak monitoring and documentation systems, which have resulted in many PSU assets being poorly recorded. The introduction of SIPSUPER is expected to serve as a technology-based public service innovation that enhances transparency, accountability, and effectiveness in PSU management. The study adopts a quantitative approach with descriptive analysis and simple linear regression. Data were collected through questionnaires, field observations, and document reviews, then analyzed using validity and reliability tests as well as hypothesis testing. The results indicate that the implementation of SIPSUPER has been fairly successful in supporting the processes of data collection, monitoring, and the handover of PSU from developers to the local government. Moreover, the use of SIPSUPER has shown a significant effect on improving the effectiveness of PSU management, as reflected in greater data transparency, easier access to information, and more optimal government supervision. Overall, it can be concluded that SIPSUPER contributes positively to the governance of PSU in Samarinda City.